miR-34b-3p May Promote Antiplatelet Efficiency of Aspirin by Inhibiting Thromboxane Synthase Expression - Liu, Wen Wen; Wang, Hao; Chen, Xia Huan; Fu, Sidney W.; Liu, Mei Lin (Thrombosis and Haemostasis, 2019)
Aspirin has been widely used for the prevention of cardiovascular diseases, but its antiplatelet efficiency varies between individuals. The present study aimed to evaluate response to aspirin based on gene profiles as well as potential regulating pathways using human blood samples and cell lines. Platelet function in patients 50 years or older with coronary artery disease on 100 mg/day aspirin was measured by light transmission aggregometry (LTA) of arachidonic acid (AA)-induced platelet aggregation. The expression of eight candidate genes—PTGS1/COX1, PLA2G4A, PLA2G6, PLA2G7, TBXAS1, TBXA2R, PTGIR, and ITGA2B—and the ingredients involved in AA metabolism were analyzed. Our data showed that the expressions of thromboxane A synthase 1 (TBXAS1), thromboxane synthase (TXS), and thromboxane B2 (TXB2) were increased in the upper quartile of platelet aggregation (LTA-AA_Q4) group compared with the lower quartile of platelet aggregation (LTA-AA_Q1) group. Our bioinformatics analysis suggested that TBXAS1 was targeted by miR-34b-3p via binding to its 3′-UTR, which was subsequently verified experimentally. Although overexpression of miR-34b-3p exhibited no apparent effect on cell proliferation, inhibition of miR-34b-3p promoted megakaryocyte viability. Our data demonstrated that the expression of TBXAS1 was higher in the aspirin hyporesponsiveness group than that in the hyperresponsiveness group, suggesting that high expression of TBXAS1 may be associated with aspirin hyporesponsiveness. miR-34b-3p may regulate the platelet and aspirin response by suppressing TBXAS1 expression and megakaryocyte proliferation.
Keywords: aspirin efficiency; thromboxane synthase; miR-34b-3p; megakaryocyte; coronary artery disease